The Epidemiological Characteristics of Diarrheagenic Escherichia Coli among Children with Acute Diarrhea - Ayesha Masood, Hassan Raza Heral, Fatima Masood, Sehr Imran, Zuhaib Farooq, Syed Zeeshan Haider Naqvi (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Diarrhea is known as one of the highly infectious diseases affecting the world population around the globe especially the children community. It is associated with the highest mortality and morbidity rates in children. Objective: The study was carried out to find the characteristic features of diarrheagenic Escherichia coli among children with acute diarrhea under the age of 5 years. Study design: It is a prospective based study conducted for the duration of the one year from September 2021 to August 2022. Material and Methods: There were 130 patients that participated in this study. The samples were collected from each patient. The clinical symptoms and demographic features of each patient were recorded. The SPSS was used for statistical analysis. Results: Some of the features that were commonly observed among children were nausea (n=23), vomiting (n=32), abdominal pain (n=60) and fever (n=12). There were 27% patients that reported diarrhea in spring, 26% in autumn, 33% and 12% in summer and winter respectively. It was found that the isolate rate was decreasing in the order from EPEC, EAEC, ETEC, STEC and EIEC in age group 0-11. Conclusion: This study reported that EPEC is an important phenotype present among children under the age of 5 who are suffering from DEC infection. The drug resistance cases are increasing in DEC strains with time. The antibiotic resistance was shown for ampicillin in both DEC strains and the aEPEC subtype. The data can be used to study the antimicrobial investigation against these strains. Keywords: Escherichia coli.